Susceptibility profile and epidemiological cut-off values of Cryptococcus neoformans species complex from Argentina - Córdoba, Susana (2016)
Fil: Córdoba, Susana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.